Refugee protection norms and the fragmented refugee regime in Southeast Asia - Raquinio, Tezla Gael G. (Animo Repository, 2023)
From 2012 to 2015, the Southeast Asian region witnessed the worst refugee crisis in its history since the Vietnam war – the Rohingya crisis. The crisis was triggered by the exodus of the Muslim ethnic minority Rohingya from Myanmar and was exacerbated by Thailand’s crackdown on human trafficking rings. The Rohingya crisis presented an opportunity for the Southeast Asian region to develop its own refugee protection regime. However, despite the crisis, the region remains to have “the weakest normative refugee protection framework” in the world. Thus, this study aims to explain why the refugee regime in Southeast Asia remains underdeveloped. To achieve this end, the paper analyses the events that transpired, on a national and regional level, from 2012 to 2015 using Martha Finnemore and Kathryn Sikkink’s norm life cycle model. This paper argues that the refugee regime in Southeast Asia remains underdeveloped because Malaysia, Thailand, and Indonesia as well as the Association of Southeast Asian Nations (ASEAN) were able to preserve the status quo during the Rohingya crisis. The states were able to deal with domestic and international pressure through existing policies which resulted in the lack of motivation to adhere to refugee protection norms. At the same time, there was inadequate pressure for the states to adapt international refugee protection norms during the crisis. Meanwhile, on a regional level, the ASEAN was paralysed by the non-interference principle to directly address the crisis and at the same time, the involvement of human trafficking rings in the Rohingya crisis made it possible for the regional bloc to deal with the crisis in the anti-human trafficking dimension, instead of the refugee protection dimension. As long as the refugee regime in Southeast Asia remains underdeveloped, refugee protection will remain fragmented, which will continue to make the situation of refugees in the region precarious.